Delayed Graft Function in Kidney Transplants: Time Evolution, Role of Acute Rejection, Risk Factors, and Impact on Patient and Graft Outcome. (10th September 2015) - Chaumont, Martin; Racapé, Judith; Broeders, Nilufer; El Mountahi, Fadoua; Massart, Annick; Baudoux, Thomas; Hougardy, Jean-Michel; Mikhalsky, Dimitri; Hamade, Anwar; Le Moine, Alain; Abramowicz, Daniel; Vereerstraeten, Pierre
Abstract : Background . Although numerous risk factors for delayed graft function (DGF) have been identified, the role of ischemia-reperfusion injury and acute rejection episodes (ARE) occurring during the DGF period is ill-defined and DGF impact on patient and graft outcome remains controversial. Methods . From 1983 to 2014, 1784 kidney-only transplantations from deceased donors were studied. Classical risk factors for DGF along with two novel ones, recipient's perioperative saline loading and residual diuresis, were analyzed by logistic regression and receiver operating characteristic (ROC) curves. Results . Along with other risk factors, absence of perioperative saline loading increases acute rejection incidence (OR = 1.9 [1.2–2.9]). Moreover, we observed two novel risk factors for DGF: patient's residual diuresis ≤500 mL/d (OR = 2.3 [1.6–3.5]) and absence of perioperative saline loading (OR = 3.3 [2.0–5.4]). Area under the curve of the ROC curve (0.77 [0.74–0.81]) shows an excellent discriminant power of our model, irrespective of rejection. DGF does not influence patient survival( P = 0.54 ) . However, graft survival is decreased only when rejection was associated with DGF( P < 0.001 ) .   Conclusions . Perioperative saline loading efficiently prevents ischemia-reperfusion injury, which is the predominant factor inducing DGF. DGF per se has no influence on patient and graft outcome. Its incidence is currently close to 5% in our centre.